Cognitive Performance of Wild Eastern Gray Squirrels (Sciurus carolinensis) in Rural and Urban, Native, and Non-native Environments - Chow, Pizza Ka Yee; Clayton, Nicola S.; Steele, Michael A. (Frontiers in Ecology and Evolution, 2021)
Enhanced cognitive ability has been shown to impart fitness advantages to some species by facilitating establishment in new environments. However, the cause of such enhancement remains enigmatic. Enhanced cognitive ability may be an adaptation occurring during the establishment process in response to new environments or, alternatively, such ‘enhancement’ may merely reflect a species' characteristic. Based on previous findings that have shown ‘enhanced’ cognitive ability (i.e., higher success rate in solving novel food-extraction problems or, ‘innovation’) in Eastern grey squirrels (Sciurus carolinensis), a successful mammalian invader and urban dweller, we used an intraspecific comparative paradigm to examine the cause of their ‘enhanced’ cognitive ability. We conducted a field study to compare cognitive performance of free-ranging squirrels residing in rural and urban habitats in native (US) and non-native environments (UK). By using established tasks, we examined squirrels’ performance in easy and difficult, novel food-extraction problems (innovation), a motor memory recall test of the difficult problem, and a spatial learning task. We found that the four groups of squirrels showed comparable performance in most measures. However, we also found that the native urban squirrels showed: 1) higher success rate on the first visit for the difficult problem than the non-native urban squirrels; 2) some evidence for higher recall latency for the difficult problem after an extended period than the non-native rural squirrels; and 3) learning when encountering the same difficult problem. These results suggest that the previously reported ‘enhanced’ performance is likely to be a general characteristic and thus, a pre-adaptive phenotypic trait that brings fitness advantages to this species in a new environment. Despite this, some cognitive abilities in grey squirrels such as solving novel problems has undergone mild variation during the adaptive process in new environments.